2012
DOI: 10.1002/arch.21017
|View full text |Cite
|
Sign up to set email alerts
|

A COMPLEX OF GENES INVOLVED IN ADAPTATION OF Leptinotarsa decemlineata LARVAE TO INDUCED POTATO DEFENSE

Abstract: The Colorado potato beetle (Leptinotarsa decemlineata) is the most important pest of potato in many areas of the world. One of the main reasons for its success lies in the ability of its larvae to counteract plant defense compounds. Larvae adapt to protease inhibitors (PIs) produced in potato leaves through substitution of inhibitor-sensitive digestive cysteine proteases with inhibitor-insensitive cysteine proteases. To get a broader insight into the basis of larval adaptation to plant defenses, we created a "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 73 publications
3
57
3
2
Order By: Relevance
“…Digestive cysteine proteases are accompanied by digestive serine and aspartic proteases in CPB larval guts [9,41,42], therefore their inhibition by clitocypin was also assessed, since they complement cysteine proteases during adaptation to dietary cysteine protease inhibitors. Clitocypin did not inhibit the chymotrypsin-like serine protease activity, measured with substrate Boc-Gly-Arg-Arg-MCA at pH 8.8 in the presence of E-64 (Fig.…”
Section: Clitocypin Inhibits Digestive Cysteine Proteases (Intestainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Digestive cysteine proteases are accompanied by digestive serine and aspartic proteases in CPB larval guts [9,41,42], therefore their inhibition by clitocypin was also assessed, since they complement cysteine proteases during adaptation to dietary cysteine protease inhibitors. Clitocypin did not inhibit the chymotrypsin-like serine protease activity, measured with substrate Boc-Gly-Arg-Arg-MCA at pH 8.8 in the presence of E-64 (Fig.…”
Section: Clitocypin Inhibits Digestive Cysteine Proteases (Intestainsmentioning
confidence: 99%
“…Profiles of gene expression in CPB larvae fed with transgenic potato leaves were monitored by isolating RNA from their midguts at day 8 of the second feeding trial, as described [9]. Six biological samples were obtained for each group by pooling midguts from two or three larval specimens from the same group for each sample.…”
Section: Analysis Of Gene Expression Of Known Adaptation-related Digementioning
confidence: 99%
See 1 more Smart Citation
“…Detailed analyses of differentially expressed transcripts showed a notable upregulation of several transcripts encoding hexamerin-like proteins, which are known to be juvenile hormone binding proteins (JHBPs)19. Interestingly, one other study performed in the Colorado potato beetle, Leptinotarsa decemlineata , also demonstrated an induced expression of several JHBPs after feeding on potato plants with induced defences16. These findings could suggest a more general role for JHBPs or JH in the regulation of the digestive process in insects.…”
mentioning
confidence: 94%
“…Like in other insects, the underlying regulatory mechanisms of this adaptation are however still unknown. Up to now, only few studies have tried to identify broader transcriptional changes associated with this phenomenon81415161718. However, these studies mostly investigated long-term changes after dietary PI uptake and did not focus on the initial driving forces regulating the response.…”
mentioning
confidence: 99%